Genetic evaluation of feed efficiency and related traits in egg type chicken*4Senior Scientist. - REDDY, B L N; SINGH, RAJVIR; KATARIA, M C; SHARMA, DEEPAK (The Indian Journal of Animal Sciences, 2014)
Feeding trial was conducted in selected line (IWH) and control line (IWC) to evaluate the status of various feed efficiency traits. The trial was cond.ucted on 24th generation of IWH and IWC lines. In IWH line feed efliciency traits like actual feed consumption (AFC), feed consumption per day, feed per dozen eggs and feed per kg egg mass were estimated. Results indicated that actual feed consumption during 37-40 weeks remained less. During peak egg production (29-32 weeks) birds consumed more teed than remaining 2 periods. Actual feed consumption; feed/day and teed/dozen eggs were medium heritable traits. Genetic correlation of age at sexual maturity with feed consumption was positive in direction and higher in magnitude. Genetic correlations of 20 weeks body weight with feed consumption at diiferent periods were positive in direction and higher in magnitude.